Strategy to Increase Shredded Patin Fish Production in the Mina Family Fish Farming Group Kandis District, Siak: Strategi Peningkatan Produksi Abon Ikan Patin Pada Kelompok Pembudidaya Ikan Mina Family Kecamatan Kandis, Siak - Maulidiah, Sri; Agusnimar, Agusnimar; Mardianty, Desy; Yuslaini, Nina; Syahruddin, Syahruddin; Ikhtiaruddin, Ikhtiaruddin (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
The Mina Family Fish Cultivation Group (POKDAKAN) is one of the new groups engaged in freshwater fish cultivation located in Simpang Belutu Village, Kandis District, Siak. In addition to being sold, the diversification of processed fish is also carried out through the production of shredded Patin Fish, but there are problems, namely the decline in the production of shredded catfish due to limited knowledge, limited technological innovation tools, and limited marketing. From the problems that occurred, there was a need for a comprehensive strategy so that it became the reason for determining the topic and location of the activity by the 2024 UIR Grant PKM Team. This activity uses the method of (1) Rapid Rural Appraisal (RRA) Method, (2) Participatory Rural Appraisal (PRA) Method, (3) Action Research Method. There are stages of PKM activities, namely surveys, socialization, counseling, training, monitoring and evaluation, and program sustainability. The solutions provided are education and training in shredded processing, provision of technological innovation tools (spinner machines), management of PIRT and NIB permits. The results of the activity are producing quality shredded fish, the availability of Spinner machines, and the issuance of PIRT and NIB permits